The European integration of RES-E promotion. The case of Germany and Poland. - Wedel, Marco (Springer VS, 2016)
By using the example of Germany and Poland this multi-level policy dependency analysis researches constraints and dependencies of the European Integration of the promotion of renewable energy source electricity (RES-E). To gain insightful results, the author does not only take a look at the implementation effectiveness of the relevant Directive 2009/28/EC, but much more generally analyses the potentially conflicting polity implications of the entities involved, as well as their respective policy preferences and processes in light of RES-(E). Combined, these give rise to multi-level constraints and dependencies for the European Integration of RES-(E) promotion.
Keywords: Energie; Energiepolitik; Energieproduktion; Alternativenergie; Förderungspolitik; Wirkung; Vergleichsuntersuchung; Erneuerbare Energie; Strommarkt; EU-Richtlinie; Politikinstrument